2003
DOI: 10.1161/01.res.0000049104.57549.03
|View full text |Cite
|
Sign up to set email alerts
|

Hibernating Myocardium Retains Metabolic and Contractile Reserve Despite Regional Reductions in Flow, Function, and Oxygen Consumption at Rest

Abstract: Abstract-Hibernating myocardium, characterized by reductions in flow and function at rest, has limited contractile reserve in response to increases in external workload. We hypothesized that this attenuation of function reflects an adaptive downregulation that prevents the development of metabolic evidence of ischemia during stress. To test this hypothesis, pigs were chronically instrumented with a proximal left anterior descending artery stenosis for 3 months, resulting in severe anteroapical hypokinesis with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
94
2
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 45 publications
12
94
2
5
Order By: Relevance
“…As in previous studies in large animals and humans (13,14,17,22), blood flow to viable portions of poststenotic myocardium in rodents is reduced, as indicated in the present study. We showed that in the rat heart, poststenotic MR perfusion was significantly reduced, with a good correlation between MR perfusion and MS blood flow.…”
Section: Discussionsupporting
confidence: 87%
“…As in previous studies in large animals and humans (13,14,17,22), blood flow to viable portions of poststenotic myocardium in rodents is reduced, as indicated in the present study. We showed that in the rat heart, poststenotic MR perfusion was significantly reduced, with a good correlation between MR perfusion and MS blood flow.…”
Section: Discussionsupporting
confidence: 87%
“…Transmural MBF measurements at 6 mo using microsphere also showed that the subendocardial layer had the most significant decrease in MBF with a subsequent decrease in the endo/epi MBF ratio. The myocardial perfusion reserve was also markedly diminished in the hibernating myocardium as shown previously (12).…”
Section: Discussionsupporting
confidence: 83%
“…Thus there is a temporal progression from chronic stunning to hibernation in which the reduced resting blood flow is the result rather than the cause of chronic contractile dysfunction (3-5, 8 -9, 11-13, 23-25). Decreased myocardial oxygen consumption has been observed in hibernating myocardium at rest and during an increase in myocardial oxygen demand that contrasts with the findings in short-term hibernating myocardium (2,12). Chronic hibernating myocardium demonstrates the alteration in metabolism with an increase in glucose uptake and glycogen storage (8,13,23).…”
mentioning
confidence: 97%
“…A left thoracotomy was performed in the fourth intercostal space. The proximal LAD was dissected free and instrumented with a fixed-diameter Delrin stenosis (1.5 mm ID) (6,11,12). The chest incision was closed in layers, the intercostal nerves were infiltrated with 2% lidocaine for analgesia, and the pneumothorax was evacuated.…”
Section: Methodsmentioning
confidence: 99%